Under pressure! Team innovative climate and individual attitudes in shaping individual improvisation. Issue 4 (August 2018) - Magni, Massimo; Palmi, Pamela; Salvemini, Severino
Abstract: By embracing a perspective grounded in the Theory of Reasoned Action, this paper investigates the mechanisms through which team climate affects individual improvisation. By relying on data from 134 individuals belonging to 25 artistic collectives, our paper shows that team innovative climate impacts individual improvisation by triggering individual proactive attitude and risk aversion attitude. Because our research spans across different levels of analysis, we developed a multilevel model for analyzing our hypotheses. Our study complements the results of previous research by asserting that improvisation is not an inherently individual phenomenon; rather, improvisation is also affected by the characteristics of the team in which individuals are embedded.